Report of 17th working committee and general assembly ASEAN Inter-parliamentary organization - Asean inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 1996)
Cuộc họp ủy ban và Hội nghị lần thứ mười bảy của Tổ chức liên nghị viện ASEAN đã được tổ chức tại Phuket, Thái Lan từ ngày 16 đến 21 tháng 9 năm 1996.